ON PARETO SET FOR A BI-CRITERIA SINGLE MACHINE SCHEDULING PROBLEM - Rzgar F. Mahmood; Ayad Mohammed Ramadan; Mediya B. Mrakhan; Nasyar Hussein Qader4 (Tikrit Journal of Pure Science, 2023)
This paper considers a bi-criteria planning problems on a single machine, with the goal of minimizing total square time duration and maximizing earliness. To solve this problem we have to find the Pareto set. We introduced a strong relation between lower bound, upper bound  of the problem and the number of efficient solutions via a theorem which shows also that the lower bound is near to optimal solution if the number of efficient solutions is small.